Analisis Viktimisasi Korporasi: Perlindungan Hukum terhadap Perusahaan sebagai Korban Kejahatan Ekonomi Transnasional - gita khairunisa (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2025)
This study analyzes corporate victimization resulting from transnational economic crimes (such as CEO Fraud and industrial espionage). The main focus is to evaluate existing domestic and international legal frameworks, which are deemed inadequate in providing protection and recovery for losses. A normative juridical method is employed. The findings indicate the presence of jurisdictional gaps and slow Asset Recovery mechanisms. The study recommends an ideal legal protection model that emphasizes accelerating cross-border asset freezing measures, strengthening the proactive role of law enforcement authorities, and reforming international cooperation frameworks beyond traditional Mutual Legal Assistance (MLA) to ensure effective restitution for corporate victims.